Invariant and Absolute Invariant Means of Double Sequences - Abdullah Alotaibi; M. Mursaleen; M. A. Alghamdi (Journal of Function Spaces and Applications)
We examine some properties of the invariant mean, define the concepts of strong σ-convergence and absolute σ-convergence for double sequences, and determine the associated sublinear functionals. We also define the absolute invariant mean through which the space of absolutely σ-convergent double sequences is characterized.